Comprehensive Insights Into Forensic Features and Genetic Background of Chinese Northwest Hui Group Using Six Distinct Categories of 231 Molecular Markers - Chen, Chong; Jin, Xiaoye; Zhang, Xingru; Zhang, Wenqing; Guo, Yuxin; Tao, Ruiyang; Chen, Anqi; Xu, Qiannan; Li, Min; Yang, Yue; Zhu, Bofeng (Frontiers in Genetics, 2021)
The Hui minority is predominantly composed of Chinese-speaking Islamic adherents distributed throughout China, of which the individuals are mainly concentrated in Northwest China. In the present study, we employed the length and sequence polymorphisms-based typing system of 231 molecular markers, i.e., Amelogenin, 22 PISNPs, 94 IISNPs, 24 Y-STRs, 56 AISNPs, 7 X-STRs, and 27 A-STRs, into 90 unrelated male individuals from the Chinese Northwest Hui group to comprehensively explore its forensic characteristics and genetic background. Total 451 length-based and 652 sequence-based distinct alleles were identified from 58 STRs in 90 unrelated Northwest Hui individuals, denoting that the sequence-based genetic markers could pronouncedly provide more genetic information than length-based markers. The forensic characteristics and efficiencies of STRs and IISNPs were estimated, both of which externalized high polymorphisms in Northwest Hui group and could be further utilized in forensic investigations. No significant departure from the HWE expectation was observed after the Bonferroni correction. Additionally, four groups of reference population data were exploited to dissect the genetic background of the Northwest Hui group separately from different perspectives, which contained 26 populations for 93 IISNPs, 58 populations for 17 Y-STRs, 26 populations for 55 AISNPs (raw data) and 109 populations for 55 AISNPs (allele frequencies). As a result, the analyses based on the Y-STRs indicated that the Northwest Hui group primarily exhibited intimate genetic relationships with reference Hui groups from Chinese different regions except for Sichuan Hui group, and secondarily displayed close genetic relationships with populations from Central and West Asia, as well as several Chinese groups. However, the AISNP analyses demonstrated that the Northwest Hui group shared more intimate relationships with current East Asian populations, especially with reference Hui and Tu groups, harboring the large proportion of ancestral component contributed by East Asia.